Art past, art present - Wilkins, David G. 4 0 16; 1948- Schultz, Bernard,;Linduff, Katheryn M.; 5 (Upper Saddle River, N.J. : Pearson/Prentice Hall, 1990)
Examines the history, social concerns, and the role of artist in connection to various styles of art, architecture, film, and photography, from prehistory through modernity. Includes 760 illustrations.
Includes bibliographical references (p. 615-617) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; History.;History. -- Art;Art; 20; 2